Changes in Knowledge and Beliefs About Human Papillomavirus and Cervical Cancer Screening Intervals in Low-Income Women After an Educational Intervention. (April 2016) - Roland, Katherine B.; Benard, Vicki B.; Greek, April; Hawkins, Nikki A.; Lin, Lavinia
Introduction: Women have been reluctant to adopt longer than annual intervals for cervical cancer screening, despite guidelines recommending screening every 3 to 5 years. Our study assessed patient knowledge and beliefs about human papillomavirus (HPV) and cervical cancer screening after exposure to an educational intervention, and whether there was a change in time regarding knowledge and beliefs among all study participants in an underserved population.Method: The study was conducted in 15 clinics associated with 6 Federally Qualified Health Centers in Illinois, USA. Cervical cancer screening patients (n = 644) completed a baseline and postintervention follow-up survey. The intervention included an HPV test and an educational pamphlet. Significance testing of changes in knowledge and beliefs was conducted with multilevel, mixed-effects models adjusting for repeated measures of patients and clustering within clinics.Results: No significant differences in study outcomes were found between the intervention and control groups. Among all women, knowledge of HPV significantly improved over time. At follow-up, fewer women reported that having a co-test is good, wise, will give you peace of mind, will tell you whether you need to worry if Pap is abnormal, is something your doctor thinks you should have, and will give you the best care available. More women said it would be bad, useless, or worrying to wait 3 years for a Pap test at follow-up.Conclusion: HPV knowledge improved over time, but the educational intervention utilized in this study was not successful in improving attitudes and beliefs about co-testing and longer screening intervals, and beliefs about HPV co-testing and 3-year screening intervals were less favorable. Having health care providers discuss the consequences of overscreening and the natural history of HPV and cervical cancer with their patients may help increase adherence to longer screening intervals. Further examination of the essential components for educational intervention in this population is warranted.